1331 Percutaneous Transhepatic Ultrasound-Guided Cardiac Catheterization in a Fetal Lamb Model. (October 2012) - Edwards, A; Menahem, S; Nitsos, I; Chan, Y; Veldman, A; Schranz, D; Wong, F
Abstract : Background: Fetal cardiac intervention may alter the progression of cardiac conditions. Fetal heart access by direct puncture of the fetal heart under ultrasound guidance has been established, but with considerable technical difficulties. We aim to investigate the feasibility of fetal cardiac access using a percutaneous transhepatic approach in the mid-gestational fetal lamb, as a model for human fetus. Method: Eight fetal lambs of 95–97 days gestation (term 147 days) were studied. Under ultrasound guidance, the fetal right hepatic vein was punctured percutaneously, using a 16GA intravenous cannula (BD Angiocath). A coronary catheter (FineCross TM MG, Terumo) was inserted into the 16 GA cannula, over a 0.014inch guidewire, and advanced into the inferior vena cava and the right atrium. Contrast was injected to document position of the catheter. Three fetal lambs were to be euthanized at the end of the procedure to evaluate blood loss. The rest were to deliver vaginally at term, and euthanized for postmortem examination. Results: Percutaneous fetal cardiac access was successful in 7 out of the 8 fetuses. All 4 heart chambers were catheterized in the last 3 fetuses. One fetus died during the procedure, post-mortem showed pericardial and peritoneal haemorrhage. The other two fetuses dedicated for immediate post-mortem, after having survived the procedure, had small haemoperitoneum. Averaged fetal weight was 1027±153g. All other lambs were born normally at term. Conclusion: Ultrasound-guided fetal cardiac catheterization through a percutaneous transhepatic approach is feasible. Our experience provides a potentially safer route for human fetal cardiac intervention at midgestational age.